A Review of Sentiment Analysis in Spanish - Henríquez Miranda, Carlos; Guzmán, Jaime (TECCIENCIA, 2017)
Sentiment analysis is an area of research that shows an upward trend, especially in the last two years due to large -scale production of opinions and comments from users active over the Web and social networks, in general. Companies and organizations are interested in knowing of their reputation in social networks, blogs, wikis, and other Web sites. Until now, the vast majority of the work involves systems in English. For this reason, the scientific community is interested in studies in other languages. This paper provides a brief overview of the current state of sentiment analysis in Spanish language.